2015
DOI: 10.1371/journal.pone.0121674
|View full text |Cite|
|
Sign up to set email alerts
|

Multimodal Holographic Microscopy: Distinction between Apoptosis and Oncosis

Abstract: Identification of specific cell death is of a great value for many scientists. Predominant types of cell death can be detected by flow-cytometry (FCM). Nevertheless, the absence of cellular morphology analysis leads to the misclassification of cell death type due to underestimated oncosis. However, the definition of the oncosis is important because of its potential reversibility. Therefore, FCM analysis of cell death using annexin V/propidium iodide assay was compared with holographic microscopy coupled with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 46 publications
3
42
1
1
Order By: Relevance
“…Morphological changes in thyroid cancer cells that were treated with metformin in low-glucose evoked oncosis. Oncosis is considered as a multi-step process and a recent study (Balvan et al 2015) has demonstrated that oncotic and apoptotic types of cell death can be distinguished using time-lapse microscopy. The real-time imaging demonstrating that metformin induces cellular swelling, followed by cell shrinkage, membranous blebbing, cell detachment, and finally death, suggested that oncosis is a mechanism of metformin-inducible thyroid cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes in thyroid cancer cells that were treated with metformin in low-glucose evoked oncosis. Oncosis is considered as a multi-step process and a recent study (Balvan et al 2015) has demonstrated that oncotic and apoptotic types of cell death can be distinguished using time-lapse microscopy. The real-time imaging demonstrating that metformin induces cellular swelling, followed by cell shrinkage, membranous blebbing, cell detachment, and finally death, suggested that oncosis is a mechanism of metformin-inducible thyroid cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Studying cell death plays an important role in understanding tissue homeostasis, for example, embryo development , and in inferring efficacy of cancer treatment . Among available methods, cellular morphology assessment is so far one of the most effective methods to investigate cell death . Here, we employ high speed FACED imaging flow cytometry of THP‐1 cells to study starvation‐induced cell death for 6 days at single‐cell precision.…”
Section: Resultsmentioning
confidence: 99%
“…Similar trend, albeit less significant, can be observed in cell circularity. These biophysical changes of cells signify the known apoptotic response of cells . We further investigate the biomolecular (i.e., lysosomal) response obtained from the spatial distribution of neutral red within individual cells.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Apoptosis, a programmed cell death, manifest features of dynamic morphology as a retraction of the cell into spherical shape that shows exaggerated zeiosis, which is a fast appearing and disappearing protrusions bulging at the tips and eventually splitting off the cell to form apoptotic bodies. Complete dismantling of the cell body is a desired trait of harmless removal of cell residues, because this does not initiate inflammation.…”
Section: Criteria For Cell Death Evaluationmentioning
confidence: 99%